Efektivitas Chatbot Konseling Terhadap Kesehatan Mental Mahasiswa BPI IAIN Metro: Efektivitas Chatbot Konseling Terhadap Kesehatan Mental Mahasiswa BPI IAIN Metro - Aisyah Khumairo; Al Halik; Lilik Kusuma Ningrum; Chyntia Zahra (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2022)
This research is motivated by the increasing academic, social and personal pressure experienced by BPI IAIN Metro students in the digital era, which has a negative impact on mental health. Students often face various problems such as academic stress, confusion in choosing a career, and social pressure. The aim of this research is to measure the effectiveness of counseling chatbots in improving the mental health of students in the Islamic Counseling Guidance Study Program at IAIN Metro. The theory used involves the concept of mental health, which includes psychological well-being and psychological stress as well as cybercounseling based on artificial intelligence (AI) technology. This research is a quantitative experiment with a One Group Pretest-Posttest design to measure changes in students' stress levels and mental well-being before and after the counseling chatbot treatment. Samples were taken from BPI students who had low mental health, namely 15 students and data was collected using a Likert scale and analyzed using statistical analysis techniques. The results of the research show that chatbot counseling services are effective in improving students' mental well-being. After the intervention, there was a significant improvement in students' mental health, as evidenced by the results of the paired t-test and N-Gain test which showed a significant increase from pretest to posttest. Counseling chatbots are proving to be an innovative and practical solution to help students overcome mental health problems.